Psikologi Komunikasi Dalam Dakwah Pada Lansia (Studi Kasus Majelis Ta’lim An-Nuriyyah, Waru, Sidoarjo) - Maimunah; Lucky Prihartanto (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2026)
This study examines the communication psychology underlying the da'wah practice of Bu Nyai Ati' Nursyafa'ah at Majelis Ta'lim An-Nuriyyah, Waru, Sidoarjo, a congregation composed predominantly of women aged sixty to eighty-three. Using a descriptive qualitative design with a phenomenological method, data were gathered through participant observation, an in-depth interview with the preacher, and structured interviews with twenty congregants, then analyzed through Rakhmat's (2015) framework of communicator, communicant, and message psychology. Findings show that twenty-seven years of consistent presence produced layered credibility, similarity-based attraction, and informal charismatic authority (Hovland & Weiss, 1951; Kelman, 1958), while the personal, sociopsychological, and situational needs of elderly listeners were deliberately managed, and bilingual, multisensory, multi-layered messages addressed cognitive, affective, and conative dimensions simultaneously. Six interlocking mechanisms, trust, psychological safety, relevance, communal reinforcement, cathartic prayer, and internal opinion leadership, explain this success, demonstrating that competency-based authority outweighs age-based hierarchy in elderly-focused da'wah.